Protection of Beta Boswellic Acid against Streptozotocin-induced Alzheimerʼs Model by Reduction of Tau Phosphorylation Level and Enhancement of Reelin Expression - Shasaltaneh, Marzieh Dehghan; Naghdi, Nasser; Ramezani, Sadrollah; Alizadeh, Leila; Riazi, Gholam Hossein (Planta Medica, 2021)
Alzheimerʼs disease is a growing general health concern with huge implications for individuals and society. Beta boswellic acid, a major compound of the Boswellia serrata plant, has long been used for the treatment of various inflammatory diseases. The exact mechanism of beta boswellic acid action in Alzheimerʼs disease pathogenesis remains unclear. In the current study, the protective effect of beta boswellic acid on streptozotocin-induced sporadic Alzheimerʼs disease was surveyed. Alzheimerʼs disease model was induced using streptozotocin followed by an assessment of the treatment effects of beta boswellic acid in the presence of streptozotocin. The prevention effect of beta boswellic acid on Alzheimerʼs disease induction by streptozotocin was evaluated. Behavioral activities in the treated rats were evaluated. Histological analysis was performed. Phosphorylation of tau protein at residues Ser396 and Ser404 and the expression of reelin protein were determined. Glial fibrillary acidic protein immunofluorescence staining was applied in the hippocampus regions. Our findings indicated that beta boswellic acid decreased traveled distance and escape latency in the prevention (beta boswellic acid + streptozotocin) and treatment (streptozotocin + beta boswellic acid) groups compared to control during the acquisition test. It increased “time spent” (%) in the target quadrant. Reelin level was enhanced in rats treated with beta boswellic acid. Tau hyperphosphorylation (p-tau404) and glial fibrillary acidic protein were decreased in the prevention group while the expression of reelin protein in both groups was increased. We could suggest that the anti-inflammatory property of beta boswellic acid is one of the main factors involving in the improvement of learning and memory in rats. Therefore the antineurodegenerative effect of beta boswellic acid may be due to its ability to reactivate reelin protein.
Keywords: hyperphosphorylation of tau; Alzheimerʼs disease; streptozotocin; neuroprotective; anti-amnesic effect; paired helical filaments